PERAN BAHASA DALAM KOMUNIKASI POLITIK - Christina Purwanti (Jurnal Visi Komunikasi, 2021)
The existence of language in political communication is very interesting to study. Language is no longer viewed neutrally. The meaning of words, phrases, clauses, sentences, and paragraphs must be understood and understood more than literal meaning, literal meaning, or grammatical meaning. The meaning of language is always obedient to its users in political communication. It can be said that in the practice of political communication, language is always used which is very dynamic and flexible according to the context, situation, and goals of the communicator. Language has power in political communication.  Language, on the one hand, has the meaning of agreement as an instrument and expresses symptoms that occur socially which are always free from intervention by power. On the other hand, language can be an instrument capable of presenting itself and providing space and as an arena for various interests and powers. Thus, the existence of language becomes symbols and signs that always present a very specific interest in political communication. Language can shape and educate all human life. In political communication, language is not a neutral tool. Language has the power to always change, the power of language that can destroy, and also can  build. So language has a very prominent power in meaning, value, and purpose in the language itself in communicating. Here the level of language use begins to shift; starting from the use of words, the use of statements, the use of text and finally the context itself. In other words, more clearly, the words in the language of a ruler or those who are in power must be able to relate to the context. Likewise, statements in language as a ruler must also be in accordance with the context; Likewise a text that is displayed in the news, in addition to the autonomy of a text, the text must also originate from a context. Language and political communication are highly dependent on “words”, “sentences”, “text” and “context”. the essence of political communication, the expression of the truth of human life as a human being as a communicant in a society that uses a very diverse language in which it is a creature that speaks, a creature who speaks, a creature that has an interest in political communication. Language has power in political communication. This article is written to describe the existence of language in political communication using an interdisciplinary approach.